2022
DOI: 10.1186/s13195-022-00986-w
|View full text |Cite
|
Sign up to set email alerts
|

What’s the cut-point?: a systematic investigation of tau PET thresholding methods

Abstract: Background Tau positron emission tomography (PET) is increasing in popularity for biomarker characterization of Alzheimer’s disease (AD), and recent frameworks rely on tau PET cut-points to stage individuals along the AD continuum. Given the lack of standardization in tau PET thresholding methods, this study sought to systematically canvass and characterize existing studies that have derived tau PET cut-points and then directly assess different methods of tau PET thresholding in terms of their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Tau-PET patterns on the discrete scale may be influenced by the relatively lenient cutpoints used in our study. Given the large range of tau-PET cutpoints reported in the literature, future studies should focus on continuous characterization where possible or apply standardized thresholds [ 58 ]. Although we tracked the longitudinal atrophy changes relative to baseline tau pathology, we could not assess longitudinal tau-PET changes due to the limited samples of longitudinal tau-PET in the ADNI.…”
Section: Discussionmentioning
confidence: 99%
“…Tau-PET patterns on the discrete scale may be influenced by the relatively lenient cutpoints used in our study. Given the large range of tau-PET cutpoints reported in the literature, future studies should focus on continuous characterization where possible or apply standardized thresholds [ 58 ]. Although we tracked the longitudinal atrophy changes relative to baseline tau pathology, we could not assess longitudinal tau-PET changes due to the limited samples of longitudinal tau-PET in the ADNI.…”
Section: Discussionmentioning
confidence: 99%
“…Participant‐specific volume of interest (VOI) images with the subcortical and cortical regions were obtained by processing magnetic resonance (MR) images using FreeSurfer 5.3 (Massachusetts General Hospital, Harvard Medical School; http://surfer.nmr.mgh.harvard.edu), 27 which was coregistered to individual MR images within the FreeSurfer surface. A/T/N status was determined by applying a validated method as reported previously (see Supplementary Method 4 for details) 28–32 …”
Section: Methodsmentioning
confidence: 99%
“…A/T/N status was determined by applying a validated method as reported previously (see Supplementary Method 4 for details). [28][29][30][31][32]…”
Section: Image Processing Data Analysis and Determination Of A/t/n Bi...mentioning
confidence: 99%
“…A study found cognitively unimpaired individuals positive for tau and amyloid were at high risk for cognitive decline in the short term, with tau burden in the MTL and neocortex region displaying a substantial additional risk (Ossenkoppele et al, 2022). Despite its utility, limitations of tau imaging include reports of in vivo off-target binding (Smith et al, 2022), variability of thresholds for tau positivity rates between studies (Weigand et al, 2022), and similarly as with amyloid, a positive tau marker alone is not sufficient for an AD diagnosis.…”
Section: Positron Emission Tomographymentioning
confidence: 99%